Beginning C# 7 Programming with Visual Studio 2017 - Perkins, Benjamin; Hammer, Jacob Vibe; Reid, Jon D. (Indianapolis, IN : John Wiley and Sons, Inc. : Wrox, 2018)
Written in a friendly, mentor-style fashion, with each chapter building on previous ones, this book is full of helpful hints, tips, exercises, and full-fledged example code, and will teach you about all aspects of C# programming quickly and easily. --
The Main() FunctionStruct Functions; Overloading Functions; Using Delegates; Chapter 7: Debugging and Error Handling; Debugging in Visual Studio; Debugging in Nonbreak (Normal) Mode; Outputting Debugging Information; Tracepoints; Diagnostics Output Versus Tracepoints; Debugging in Break Mode; Entering Break Mode; Monitoring Variable Content; Stepping through Code; Immediate and Command Windows; The Call Stack Window; Error Handling; try ... catch ... finally; Throw Expressions; Listing and Configuring Exceptions; Chapter 8: Introduction to Object-Oriented Programming.
Online resource; title from PDF title page (EBSCO, viewed March 27, 2018).
Keywords: Microsoft Visual studio; C# (Computer program language); Electronic books